Respuesta :

The correct answer is:  [A]:  " 4x³  + x²  +  x  +  3 " .
______________________________________________________
Explanation:
______________________________________________________

(3x³ + 2x² + 2x + 1) + (x³ − x² − x + 2) = 

↔  (x³ − x² − x + 2) + (3x³ + 2x² + 2x + 1) =

(x³ − x² − x + 2) + (3x³ + 2x² + 2x + 1) = 

x³ − x² − x + 2 + 3x³ + 2x² + 2x + 1 ; 

Combine the "like terms" ; 

  x
³  +  3x³     =  + 4x³  ; 

−x²  + 2x²  =  + x²  ;

− x  + 2x    =  + x  ;
 
+ 2  + 1  =  + 3  ;
_____________________________________________________

And rewrite:
_____________________________________________________

 →  " 4x³  + x²  +  x  +  3 " ; 

 →  which is:  "Answer choice:  [A]:  " 4x³  + x²  +  x  +  3 " .
_____________________________________________________